2006
DOI: 10.1007/s10512-006-0089-1
|View full text |Cite
|
Sign up to set email alerts
|

Reactor with a fast-resonance neutron spectrum, cooled by supercritical-pressure water with a bidirectional coolant flow scheme

Abstract: A scheme for circulating coolant and cooling the core that has advantages over the designs of similar nuclear power systems is proposed for light-water reactors with supercritical coolant parameters and a fast-resonance neutron spectrum. A negative void coefficient of reactivity is obtained for the entire run of a fuel assembly without building a blanket. A more uniform distribution of the energy release over the core volume is achieved without using complicated fuel-enrichment schemes. The nonuniformity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Increasing the coolant pressure to 25 MPa and the reactor outlet coolant temperature to 550 °C increases the thermal efficiency of the units (up to 45%) and reduces the environmental impact by reducing heat losses in the thermodynamic cycle from 67% (WWER-1000) to 55% (WWER SWC) [ 1 , 2 , 3 , 4 , 5 ]. Another advantage of SWCR is the possibility of different active core designs: with a thermal neutron spectrum for operation in an open fuel cycle with UO 2 fuel and with a fast neutron spectrum for operation in a closed fuel cycle with MOX fuel [ 6 ]. So, it is important to identify candidate materials for the SWCR and validate the safety and effectiveness of their use.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the coolant pressure to 25 MPa and the reactor outlet coolant temperature to 550 °C increases the thermal efficiency of the units (up to 45%) and reduces the environmental impact by reducing heat losses in the thermodynamic cycle from 67% (WWER-1000) to 55% (WWER SWC) [ 1 , 2 , 3 , 4 , 5 ]. Another advantage of SWCR is the possibility of different active core designs: with a thermal neutron spectrum for operation in an open fuel cycle with UO 2 fuel and with a fast neutron spectrum for operation in a closed fuel cycle with MOX fuel [ 6 ]. So, it is important to identify candidate materials for the SWCR and validate the safety and effectiveness of their use.…”
Section: Introductionmentioning
confidence: 99%
“…The computational methods and algorithms which have been developed can be used to make a quantitative evaluation of the range of variation of the natural frequency of the coolant pressure oscillations for VVER-1700 (reactor with a fastresonance neutron spectrum) and VVER-1200 (reactor with a thermal neutron spectrum). The data of [8,9] are used to determine the particulars of the appearance of resonance between the acoustic oscillations of the coolant and the vibrations of the in-vessel apparatus, fuel assemblies, and fuel elements in these reactors as compared with VVER-1000. Diagram showing the cooling of a reactor with a fast-resonance neutron spectrum VVER-1700: 1) safety and control rods; 2) cover; 3) inner cover; 4) vessel; 5) thermal insulation; 6, 7) in and out pipe connections, respectively; 8) core; 9) shaft; 10, 11) descending and ascending sections, respectively; 12) separation shell.…”
mentioning
confidence: 99%
“…The thermohydraulic parameters in the fuel assembly model over the height of the core are taken from the data of [9]; the construction and dimensions of the reactor vessel and in-vessel elements, cartogram of the core, and dimensions of the fuel assemblies and fuel elements are taken to be as close as possible to the VVER-1000 characteristics.…”
mentioning
confidence: 99%
“…In a reactor with a thermal neutron spectrum, the cold moderator is confined inside tubes -"water elements" between which the fuel elements, cooled by the ascending coolant, are arranged in a closely spaced lattice. A difficulty is smoothing the energy-release field, since the moderator is substantially heated and its density varies along the height of the core.For reactors with a fast neutron spectrum, it is suggested that a bidirectional cooling scheme be used to smooth the energy release over the core height [3,4].In the present article, we present the results of a physical calculation, performed using different program systems, and a comparative analysis of a reactor with a thermal neutron spectrum with uni-and bidirectional cooling schemes. Uranium-plutonium-thorium fuel loads are considered.…”
mentioning
confidence: 99%
“…For reactors with a fast neutron spectrum, it is suggested that a bidirectional cooling scheme be used to smooth the energy release over the core height [3,4].…”
mentioning
confidence: 99%